Tradeoff between agriculture and forest preservation in the brazilian Amazon - Silva, Felipe de Figueiredo (2017)
The Brazilian Amazon forest region has experienced agricultural area expansion with high rates of progressive technical change as well as deforestation over the last decade. This has generated concern about the tradeoff between forest preservation and production of agricultural commodities. The literature suggests specifically grains, livestock and timber as the main drivers of deforestation in this region. In this study we estimate the tradeoff between agriculture and forest preservation in municipalities of the Legal Amazon for 2006 and their rate and biases in technical change during the period 2003-2015. To obtain these estimates, we use a directional distance function to estimate a production possibility frontier, considering deforestation as an undesirable output. Using this information we calculate the shadow price of reducing deforestation in terms of agricultural income foregone. Results indicate that, to preserve an average hectare of forest, US$ 796.81 in annual agricultural GDP has to be foregone. At a social discount rate of 10% and a conservative estimate of 100 tons of carbon per hectare of forest, these results imply an average shadow price of US$21.71 per ton of CO 2 emissions. This estimate varies with assumptions on discount rate, carbon content and length of period considered. We have also estimated an average rate of technical change of about 4.6% per year during the period 2003-2015. It means that, with no change in inputs, technical change allowed an expansion of agricultural outputs and a contraction of deforestation of 4.6 % during this period. Technical change has been biased toward agricultural outputs and against deforestation suggesting that increases in output are now possible with less deforestation.